Vernacular Image of the Devil in the Medieval Writings from the 13th Century and the Lithuanian Folklore: Similarities and Differences - Ščavinskas, Marius (Tautosakos darbai, 2024)
In the Middle Ages, both theological and vernacular images of the devil were formed. The theological image is rooted in the Holy Scripture, while the vernacular one, although related to the Bible, is less theological and emphasizes the “mundane” relationship between humans and the devil. Both images coexisted and did not contradict each other. The article examines the vernacular image of the devil as presented in two works from the 13th century – namely, the “Dialogues on Miracles” (Dialogus miraculorum) by Caesarius of Heisterbach, completed around 1223, and “The Great Mirror” (Speculum maius) by Vincent of Beauvais, written between 1235 and 1264. The author of the article attempts to find medieval stories (plots) regarding the devil that are similar to the ones found in the Lithuanian folklore, and to establish their differences.
Keywords: devil; vernacular image of the devil; Caesarius of Heisterbach; Vincent of Beauvais; Lithuanian folklore; the Middle Ages